A microstructural hydration model for cemented paste backfill considering internal sulfate attacks. (30th June 2019) - Liu, Lang; Zhu, Chao; Qi, Chongchong; Zhang, Bo; Song, Ki-Il
Graphical abstract: Highlights: A microstructural hydration model was proposed for CPB considering ISA effects. The ISA model was explained in detail with the basic knowledge of sulfate attack. The proposed ISA model was verified with experimental observations. Microstructural and strength evolution of CPB can be explained by the ISA model. The ISA model can be easily implemented in PFC simulation. Abstract: Cemented paste backfill (CPB) is a type of cementitious material produced with tailings, cement, and water. Typically, CPB has a high proportion of tailings (75–80 wt%), which may contain a large amount of sulfide minerals that can cause serious attacks in the CPB system. In this study, we proposed a microstructural hydration model to investigate the influence of internal sulfate attacks (ISA) on CPB. The ISA model was verified using experimental observations and was used to investigate the microstructure and strength evolution of CPB. Finally, the proposed ISA model was implemented in PFC2D to analyze the failure mode of CPB during uniaxial compressive loading. The results of the proposed ISA model agreed well with the experimental observations. Based on this model, the microstructure evolution of CPB can be classified into solid–liquid two-phase stage and solid-phase stage. Under the influence of ISA, the short-term CPB strength (≤28 days) increased at an accelerated rate whereas the long-term CPB strength (≥56 days) decreased, which could be well explained by the proposed ISA model. The PFC2D simulation results had a good agreement with those of the experiment, and the failure mode of the CPB specimen under the influence of ISA was mainly tensile.